Challenges in health and development from global to community perspectives - Johnson, Sandy A.; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
At the turn of the 21st century, human health and economic growth are inextricably linked components of international development. Challenges in Health and Development is a primer on the changing configurations of population health and economic growth in development policy. It examines strategies of investing in human health and investing in economic growth as distinct approaches to development, explores the symbiotic relationship of these tactics, and considers the applications and outcomes from a global, national and community level perspective. Each chapter introduces concepts of economic development and population health, and uses case studies to illustrate the same. These case studies include program and policy examples from Bangladesh, Chile, Haiti, Rwanda, South Africa and Sri Lanka. This text examines the impact of macroeconomic adjustment programs, health care restructuring, investment in primary health care, public-private partnerships, and the challenges of program coordination and up-scaling in stable and conflict-ridden countries. Discussion questions are provided at the end of each chapter to facilitate classroom activities. About the Author Sandy Johnson is Director of the B.A. Program in International Studies at the Josef Korbel School of International Studies, University of Denver. She earned her Ph.D. from Tulane University.
Chapter One -- 1.1.Industrial expansion, globalization and population health. The cases of England and Panama -- 1.2 Comparative measurement of health and development -- 1.3 A century's worth of global change in development and health -- 1.4 What accounts for the difference in regional change -- 1.4.1 Standard of living -- 1.4.2 Public investment, health infrastructure, and public health campaigns -- 1.4.3 Medical innovations -- 1.4.4 Technological Innovation -- 1.4.5 Behavior change -- 1.4.6 Access to care -- 1.4.7 Political will -- 1.5 A model for exploring health and development -- 1.6 Conclusion -- Chapter Two -- 2.1 Health and development as concepts in the international system -- 2.1.1 International health before WWII -- 2.1.2 The United Nations and the modern story of health and development -- 2.2 The World Health Organization -- 2.2.1 WHO early years: Health as a biomedical condition -- 2.2.2Malaria and smallpox campaigns -- 2.2.3 WHO: Health as a human right -- 2.2.3.1 Primary Health Care -- 2.2.4 Social determinants of health and the WHO in the 21st century -- 2.3 The World Bank -- 2.3.1 The World Bank: Evolution of Development -- 2.3.1.1 Structural Adjustment Program -- 2.3.1.2 World Bank as a health authority - World Development Report 1993 -- 2.3.1.3 Towards change -- 2.4 The beginning of convergence - State and human security -- 2.5 True convergence and the way forward in the 21st Century -- 2.6 Conclusion -- Chapter Three -- 3.1 Trade-offs between internal and external factors, social and economic out-comes -- 3.2 Health inputs -- 3.3 Chile Economic growth without equity -- 3.4 Sri Lanka Equity without growth -- 3.5 Conclusion -- Chapter Four -- 4.1 The importance of community -- 4.1.1 Community-based health care -- 4.1.2 Pholela Health Center - An early innovator -- 4.1.3 Gonoshasthaya Kendra, A continuing success -- 4.1.4 Implications for local health and national development -- 4.2 Microcredit and microfinance -- 4.2.1 Grameen Bank, early innovator and continuing success -- 4.2.2 Implications for development and well-being -- 4.3 Conclusion -- Chapter Five -- 5.1 Development, failed states and states in conflict -- 5.1.1 Issues of health -- 5.1.2 Refugees and IDPs -- 5.1.3 Long term impacts -- 5.2 The challenge of rebuilding -- 5.2.1 Building dependency -- 5.3 The pros and cons of scaled approaches -- 5.4 Haiti, Partners in Health /Zanmi Lasante -- 5.5 Rwanda rising from the ashes -- 5.6 Conclusion -- Chapter Six -- 6.1 Global Public-Private Partnerships -- 6.1.1 GPPPs, global research and clinical trials -- 6.2 Methods of the GPPPs -- 6.3 Examples of Recent GPPPs -- 6.4 Pros and cons of GPPPs -- 6.5 Conclusion -- Chapter Seven -- 7.1 Conclusion -- Chapter Eight: Answer key for discussion questions -- Chapter One Questions -- Chapter Two Questions -- Chapter Three Questions -- Chapter Four Questions -- Chapter Five Questions -- Chapter Six Questions -- Index.
Electronic reproduction.
Keywords: Medical policy -- Developing countries -- Case studies; Developing countries -- Social conditions -- Case studies; Developing countries -- Economic conditions -- Case studies; World Health Organization; Economic development; Health policy; International cooperation; Electronic books